Comparison of the Clinical Effects of Open and Closed Chain Exercises after Medial Patellofemoral Ligament Reconstruction - Zhang, Feng; Wang, Fei; Wang, Jun (Journal of Physical Therapy Science, 2014)
[Purpose] To compare the effects of open-chain exercise (OCE) and closed-chain exercise (CCE) for patients after medial patellofemoral ligament (MPFL) reconstruction. [Subjects and Methods] Forty patients after MPFL reconstruction were randomly divided into an OCE group and a CCE group. All the patients were evaluated at four different time points. [Results] The mean change of thigh circumference decrease in the CCE group was lower than that in the OCE group at both the 3rd and 6th month after surgery. The Lysholm score of the CCE group was higher than that of the OCE group at both the 3rd and 6th month. At the 3rd month after surgery, the visual analog scale score of the CCE group was lower than that of the OCE group. [Conclusion] CCE is better than OCE for both short and long term outcomes of patients after MPFL reconstruction.